How Reliable Is Endoscopic Scoring of Postoperative Recurrence in Crohn Disease?: A Systematic Review and Meta-Analysis - Eline M. L. van der Does de Willebois, MD; Vittoria Bellato, MD; Marjolijn Duijvestein, MD, PhD; Susan van Dieren, MD, PhD; Silvio Danese, MD, PhD; Pierpaolo Sileri, MD, PhD; Christianne J. Buskens, MD, PhD; Andrea Vignali, MD, PhD; Willem A. Bemelman, MD, PhD (Annals of Surgery Open)
Objective:. Guidelines advise to perform endoscopic surveillance following ileocolic resection (ICR) in Crohn disease (CD) for timely diagnosis of recurrence. This study aims to assess the variation in endoscopic recurrence (ER) rates in patients after ICR for CD using the most commonly used classification systems, the Rutgeerts score (RS) and modified Rutgeerts score (mRS) classifications. Methods:. A systematic literature search using MEDLINE, Embase, and the Cochrane Library was performed. Randomized controlled trials and cohort studies describing ER < 12 months after an ICR for CD were included. Animal studies, reviews, case reports (<30 included patients), pediatric studies, and letters were excluded. The Newcastle–Ottawa Quality Assessment Scale and Cochrane Collaboration’s tool were used to assess risk of bias. Main outcome was the range of ER rates within 12 months postoperatively, defined as RS ≥ i2 and/or mRS ≥ i2b. A proportional meta-analysis was performed. The final search was performed on January 4, 2022. The study was registered at PROSPERO, CRD42022363208. Results:. Seventy-six studies comprising 7751 patients were included. The weighted mean of ER rates in all included studies was 44.0% (95% confidence interval, 43.56–44.43). The overall range was 5.0% to 93.0% [interquartile range (IQR), 29.2–59.0]. The weighted means for RS and mRS were 44.0% and 41.1%, respectively. The variation in ER rates for RS and mRS were 5.0% to 93.0% (IQR, 29.0–59.5) and 19.8% to 62.9% (IQR, 37.3–46.5), respectively. Within studies reporting both RS and mRS, the weighted means for ER were 61.3% and 40.6%, respectively. Conclusions:. This study demonstrates a major variation in ER rates after ICR for CD, suggesting a high likelihood of inadequate diagnosis of disease recurrence, with potentially impact on quality of life and health care consumption. Therefore, there is an important need to improve endoscopic scoring of recurrent disease.